Peramalan Permintaan FP Flooring Jati Pada Perhutani KBM Industri Kayu Gresik Menggunakan Metode Single Moving Average - Fakhrina Triafida; Aniza Hanjas Putri; Dita Rosyita (Jurnal Logic: Logistics & Supply Chain Center, 2026)
The wood processing industry is a strategic sector supporting the national economy. Perum Perhutani KBM Industri Kayu faces challenges in the form of uncertain fluctuations in demand for Finished Product (FP) Teak Flooring, which risks causing overstock or shortages. This study aims to forecast demand for FP Teak Flooring products at Perum Perhutani KBM Industri Kayu in order to optimize production planning and inventory management. The method used in this study is a quantitative approach by utilizing secondary time series data in the form of product demand volume for five years. The data was analyzed using the Single Moving Average (SMA) forecasting method by comparing the period parameters (n) = 2 and (n) = 3. Evaluation of model accuracy was measured using the Mean Error (ME), Mean Absolute Deviation (MAD), Mean Squared Error (MSE), and Mean Absolute Percentage Error (MAPE) indicators. The results showed that the 2-SMA method had a smaller error value compared to the 3-SMA method, so it was chosen as the best model. The MAPE values ​​of both methods were in the range of 20–50%, a good forecasting capability category. The projected demand for the next five years is 3,723 m3 in 2027, decreasing to 3,288 m3 in 2028, then increasing again to 3,505 m3 in 2029. The following year it will decrease again to 3,396 m3 and increase slightly in 2031 to 3,451 m3.